Invasive marine macroalgae and their current and potential use in cosmetics - McReynolds, Colin (2017)
With increasing interconnectivity, human population growth along coastlines and changing climate, nearshore ecological assemblages are being modified at an unprecedented rate. These changes are bringing to light widespread proliferations of macroalgae, with various effects on the affected ecosystems. However, this abundance may also present opportunities. The production of cosmetics, and particularly those from natural origin, is in high demand. Many of the invasive species have demonstrated biological activity that can be applied to skin care products, so-called ‘cosmeceuticals’. A survey of common ‘invasive’ species revealed 47 species, 16 Chlorophyta, 19 Rhodophyta and 12 Phaeophyta. Their effects are interlinked but the most commonly recorded effect was habitat change, followed change of ecosystem processes, and finally genetic effects. Economic effects are difficult to quantify, containment and/or early eradication are the most effective. Re-using algae from containment programs could help finance these operations, or be an added incentive for their harvest. A literature review was from performed total of 198 articles on the recorded biological activity in humans for every species on the list; antioxidant, antibacterial, anti-inflammatory, antifungal/ antiprotozoal, antiviral, cytotoxicity/ antiproliferative, adipogenesis, MAA/ UV protection, matrix metalloproteinases, and blood fluidity were the main subjects. Most of the species on the list have been investigated for use, with only 3 unexamined, predominantly from species of small size that are difficult to identify without special equipment/ training. The major types of compounds responsible for observed activity were reviewed, with many being particular to one type of macroalgae. Intellectual property on the species was reviewed using Patentoscope, from the world intellectual property organization (WIPO). This revealed a wealth of patents that contained mentions of almost every species of algae in the study. Using patent classification schemes, the search was narrowed down to just 12 species that are the object of dedicated patents. Undaria pinnatafida and Ulva lactuca are the most commonly studied. Macroalgae can be considered a considerable source of relevant compounds for use in cosmeceuticals. Two species of invasive algae Undaria pinnatafida and Sargassum muticum were examined for their major compounds of interest, using different solvents. Extraction efficiency was solvent dependent, as well as resulting antioxidant activity. Glycerol was revealed to extract antioxidant compounds efficiently as compared to ethanol in Sargassum muticum.